Vamana Temple (Temple 5) of Cluster 2 - Temples of India Project Team (Jio Institute, 2024)
The temple has a vedibandha (basal mouldings) and a plain, unornamented jangha (wall) which is of the tri-anga (three planes of an offset) type. The shikhara (superstructure) of the temple has completely vanished, leaving only a flat roof above the garbhagriha (sanctum sanctorum).